Workshop Etika Jurnalisme Warga di Era Digital Bagi Pelajar SMA dan Mahasiswa - Djamal, Muchamad Fauzi (Universitas Prof. Dr. Moestopo (Beragama), 2022)
The current digital era and information disclosure make it easy to convey information through writing or video by disseminating it directly via the internet, especially social media. This convenience further strengthens citizen journalism, which has existed for a long time. However, citizen journalism must be accompanied by a responsibility to convey information correctly and accurately so that disinformation does not occur in society. Therefore, an understanding of ethics in disseminating information to the public must be owned when carrying out citizen journalism activities. Through training activities with the theme